Transaction Cost Analysis of ASEAN Food Security Cooperation on Rice Commodity - Pinasthika, Reni Erlita (Nation State: Journal of International Studies, 2024)
Food Security Cooperation was implemented by ASEAN through the ASEAN Economic Community (AEC), focusing on regional market integration. The food security index of its members has not been strengthened beyond the global index through this cooperation. "Special consideration," particularly concerning rice, has consistently hindered food security cooperation. Rice, being a major component of regional food cooperation and security, necessitates this explanative analysis using Transaction Cost Theory to examine the weaknesses of ASEAN Food Security Cooperation within the regional market context. Through the AEC, a nested pattern and cluster of food security issues were established by ASEAN as a key for market-based analysis. However, the failure to establish side-payments resulted in difficulties in reducing the transaction costs associated with sensitive commodities such as rice. A new perspective on sensitive commodities in the context of regional market food security cooperation is provided by this analysis. It is concluded that the weakness of food security cooperation within the regional rice market context is due to ASEAN’s inability to create side-payments and manage transaction costs that could support regional negotiations regarding rice.